THE DECLINE OF THINGNESS: REVISITING THE POSSIBILITY OF MEDIA ESCHATOLOGY - K. A. Ocheretyany (Дискурс)
This article discusses the possibility of reviving the phenomenon of “the decline of thingness”, noted by N.A. Berdyaev regarding the issue of technology in the new problematic context of epistemological and existential development of media reality. Berdyaev believed that modern technology brings destructive effects on traditional communities, nevertheless, this destructive impact is considered a productive force of technology and not a negative one. Decomposing inorganic and organic bodies, technology keeps the liberated energies on a new level in the form of organized bodies. These energies are free from thingness and open to direct experience, revealing to man the way out of the phenomenal world. In the long term, technology is capable of creating a reality that will ensure involvement with creative energies, which means liberation from space, time, objectification, and finally, from death. This is not just a question of digitizing experience and related changes, but also of the world that can be discovered with this experience. Using the language of Russian religious philosophy, Berdyaev characterized the capabilities of future technology dualistically, and in fact answered the questions posed by modern media philosophy. This questions regard the ontology of media reality, and the concepts of “creativity”, “bestialism”, “anthropogeny”, “personalistic revolution”, “organized bodies”, “machine eschatology” are revived in media reality analytics.